Some Geometric Properties of Generalized Difference Cesaro Sequence Spaces - Sengul, Hacer; Et, Mikail (Chiang Mai Univ, Fac Science, 2017)
In this paper, we define the generalized Cesaro difference sequence space C-(p) (Delta(m)) and consider it equipped with the Luxemburg norm under which it is a Banach space and we show that in the space C-(p) (Delta(m)) every weakly convergent sequence on the unit sphere converges is the norm, where p - (p(n)) is a bounded sequence of positive real numbers with p(n) > 1 for all n is an element of N.
Keywords: Cesaro difference sequence space; Luxemburg norm; extreme point; convex modular; property (H)